IMPLIKASI CSR DISCLOSURE DAN KINERJA KEUANGAN TERHADAP RETURN SAHAM (Studi Kasus Pada Perusahaan Manufaktur periode 2007-2009) - Ellyta Muchtar (Universitas Bina Sarana Informatika, 2015)
The aim of this research to find empirical evidence of the influence of CSR Disclosure and financial performance was measured with return on assets (ROA) and earning per share (EPS) on stock return.The population in this research is manufacturing companies listed on Indonesia Stock exchange (BEI) period 2007 to 2009. The samples was selected with purposive based completed of annual report company by the number of samples 60 companies. Stock return was measured based on stockmprice March and April. Analysis of the data used multiple liniear regression.The result of Adjusted R square was 0,037 and test result F was 1,746 showed that CSR disclosure, ROA and EPS had not effect to stock returns simultaneously. The based on results of t test with a standard coefficient 0,285, significant 0,046 showed that earning per share had partial effect on stock returns. Result of this study reflects that investor very heavily information about earning per share of a company to take investment decisions. Keyword : CSR disclosure, ROA, EPS, stock return